1997
DOI: 10.1046/j.1365-2958.1997.2561621.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan structure of Salmonella typhimurium growing within cultured mammalian cells

Abstract: SummaryThe cell wall structure of Salmonella typhimurium has been studied for the first time during transit from freeliving to parasitic lifestyles. Peptidoglycan of S. typhimurium proliferating within human epithelial cells contains a high proportion of previously unidentified muropeptides (5-10-fold higher than in extracellular bacteria). Amino acid and mass-spectrometry analyses showed that these new components consist of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…Thus, one possible biological role common for STM3117-3119 is to synthesize and modify the peptidoglycan layer, a major component of STM cell wall that serves as the first line of defense against the antibacterial regents produced by host cells (53). Consistent with this suggestion, prior measurements indicate that extensive peptidoglycan remodeling occurs following proliferation of STM within epithelial cells, and the peptidoglycan layer has been suggested to play an important role in mediating the infection of Salmonella (54,55). Furthermore, the composition of the peptidoglycan cell wall modulates the assembly and function of T3S (56).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, one possible biological role common for STM3117-3119 is to synthesize and modify the peptidoglycan layer, a major component of STM cell wall that serves as the first line of defense against the antibacterial regents produced by host cells (53). Consistent with this suggestion, prior measurements indicate that extensive peptidoglycan remodeling occurs following proliferation of STM within epithelial cells, and the peptidoglycan layer has been suggested to play an important role in mediating the infection of Salmonella (54,55). Furthermore, the composition of the peptidoglycan cell wall modulates the assembly and function of T3S (56).…”
Section: Discussionsupporting
confidence: 67%
“…These results indicate that the bacterial cell envelope is an important determinant for the establishment of a bacterium-host interaction. In line with this, it was observed that Salmonella enterica serovar Typhimurium peptidoglycan undergoes structural alterations that probably add to its fitness when it resides in mammalian cells (17,216).…”
Section: Genes Involved In Cell Envelope Structure and Modificationmentioning
confidence: 49%
“…2A). BLP and PGN are abundantly produced by all bacteria and are important PAMPs in bacterial-mediated diseases, including salmonellosis (46,47). It is unclear at present why galectin-3 selectively modulates some but not all TLR agonists' function.…”
Section: Discussionmentioning
confidence: 99%